(untitled) (Bangladesh Journal of Medical Science, 2012)
Objective: To evaluate growth and development of children with congenital hypothyroidism (CHT) attending Pediatric Endocrine OPD BIRDEM. Methodology: It is a cross sectional study which was conducted at Pediatric outpatient department BIRDEM in a study period of 1 year (May 2008 to April 2009). A total number of 80 children with CHT were included in the study. A data sheet was used for each subject containing all the information. History and thorough physical examination was carried out including anthropometry, and developmental assessment. Developmental assessment was done according to Denver developmental screening test using standard charts of developmental progress which is appropriate for child’s age. TSH and FT4 were done by chemiluminescent method in multichannel auto analyzer. Other investigations included bone x ray. Result: Total 80 children with congenital hypothyroidism between 1 to 5 years of age fulfilling the inclusion criteria were studied. Majority of the study population (71.20%) were diagnosed outside BIRDEM and 28.80% at BIRDEM. In the study population, 73.70% children were diagnosed within 1st three month of age and considered as early treated group, 26.20% diagnosed between three to nine month of age and classified as late treated group. Majority (56.20%) of the study population were female, and 43.70% were male child. All children among study sample were from non goiter endemic zone. Only 3 (5.0%) children among early treated group had maternal history of thyroid disorder and H/O ingestion of anti thyroid drugs and none among late treated group. 11(18.6%) early treated group and 2 (9.5%) late treated group children had affected peer with similar disorder and there was no family history of endocrine disorder among either group of study sample. Among 59 early treated group of children only 5(8.4%) had coarse facies, 2(3.3%) had protruded tongue and bradycardia, 4(6.7%) children had dry rough skin, 1(1.6%) was hypotonic, 2(3.3%) had delayed relaxation of ankle jerk and none had wide open fontanel. Out of 21 late treated group of children, 12(57.1%) had coarse facies, 4(19%) had protruded tongue, 6(28.5%) had bradycardia, 15(71.4%) children had dry rough skin, 16(76.1%) was hypotonic, 12(57.1%) had wide open fontanel and delayed relaxation of ankle jerk. Among 59 early treated group of children 53(89.8%), 51(86.4%), 55(93%) had normal and 6(10.1%), 8(13.5%), 4(6.7%) had delayed gross motor, fine motor and cognition respectively. Whereas among 21 late treated group 9(42%), 6(28.5%), 7(33.3%) had normal and 12(57%), 15(71.4%), 14(66.6%) children had delay in gross motor, fine motor and cognition respectively. There was no visual impairment among either group of children in study sample. Among 59 early treated group of children 57(96.6%) had normal hearing and 47(82.6%) had normal speech. Whereas among 21 late treated group, hearing impairment was seen among 7(25.9%) and speech delay was noticed among 16(76.1%) children. Among early treated group only 2% children had delayed radiological bone age, whereas 6% children among late treated group had delayed bone age. Conclusion: Congenital Hypothyroidism (CHT) is a serious condition of newborn babies, which leads to permanent mental and physical retardation if not identified within first few weeks of life. It is concluded that, the later the treatment is started the poorer the outcome will be. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9495 BJMS 2011; 10 (4): 245-251